Multiscale screening and identifying specific targets for artesunate in suppressing bladder cancer - Yuan, Yi; Chu, Guangdi; Ma, Qingyue; Liang, Zhijuan; Liang, Ye; Niu, Haitao (Frontiers in Pharmacology, 2025)
BackgroundBladder cancer (BLCA) is a highly aggressive urinary malignancy with high mortality in advanced stages, posing a significant health risk. Artesunate (ART), a derivative of artemisinin, has been demonstrated with potent anti-tumor activity in some studies, yet its specific targets for BLCA and the molecular mechanisms have not been fully elucidated.PurposeThis study screened potential targets of ART against BLCA through network pharmacology, followed by molecular docking simulations and experimental validation in vitro and in vivo to elucidate the underlying mechanisms.MethodsThis study identified the critical targets of BLCA and ART by employing multiscale screening from public databases, and a protein-protein interaction (PPI) network was constructed. Molecular docking simulations confirmed the stable binding of ART to the identified tumor-related targets promoting BLCA progression. These computational findings were further validated through experiments in vivo and in vitro, ensuring robust and reliable results.ResultsBased on network pharmacology analysis, the effects of ART on BLCA were multifaceted. Molecular docking simulations confirmed the binding stability of ART with core targets. The experiments in vitro proved that ART could inhibit BLCA cell proliferation and migration by downregulating the expression of BCL-2, inducing Caspase 3-mediated apoptosis, resulting in cell cycle arrest and suppressing the PI3K/Akt/mTOR classical pathway involved in BLCA growth and metabolism. Studies in vivo also confirmed that ART had significant anti-tumor effects with minimal side effects.ConclusionThis study identified the mechanism by which ART inhibited BLCA through multiple specific targets, revealing its potential anti-cancer pathways and laying the foundation for the clinical application of traditional Chinese medicine in BLCA therapy.